2011
DOI: 10.1080/02646838.2011.623227
|View full text |Cite
|
Sign up to set email alerts
|

Premature birth: subjective and psychological experiences in the first weeks following childbirth, a mixed-methods study

Abstract: Objective: The aim of the study was to explore the experience of premature infants' mothers, the way they are taken care of, how they cope with this traumatic experience as well as the psychopathological and psychosocial consequences post delivery. Method: A qualitative and quantitative study was carried out on 27 women from the south of France area who delivered preterm infants still hospitalised in a neonatal intensive care unit. Two questionnaires were completed, the IES-R and the EPDS, assessing posttrauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 14 publications
2
46
0
5
Order By: Relevance
“…This hospitalization of newborns immediately after birth is a difficult and anxiogenic situation for mothers [46,47]. The length of their stay in a hospital unit, which reflects the seriousness of their state of health, would give rise to periods of doubt as to the evolution of prematurity, disappointment with the announcement of possible complications [48] and difficulty in the development of the first links [49].…”
Section: Discussionmentioning
confidence: 99%
“…This hospitalization of newborns immediately after birth is a difficult and anxiogenic situation for mothers [46,47]. The length of their stay in a hospital unit, which reflects the seriousness of their state of health, would give rise to periods of doubt as to the evolution of prematurity, disappointment with the announcement of possible complications [48] and difficulty in the development of the first links [49].…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Themes emerging from qualitative research include the ambiguity of feeling both joy and grief, 17 comparisons made between preterm birth and the 'normal' full-term experience that mothers were denied, 18 19 and references to the cold and frightening atmosphere of the neonatal intensive care unit (NICU). 20 Few studies have examined fathers' experiences of preterm birth. One exception is a Swedish study 21 which found fathers reported three distinct experiences: (1) suddenness of the preterm birth and feeling unprepared to be a father;…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Results of neonatal parenthood studies continue to highlight the intensity of feelings that parents experience following preterm birth (Obeidat, Bond, & Clark Callister, ). These experiences can have long‐lasting social and health implications (Goutaudier, Lopez, Séjourné, Denis, & Chabrol, ; Treyvaud et al., ). However, in the past neonatal parenthood researchers infrequently reported fathers’ perspectives.…”
Section: Emotion Workmentioning
confidence: 99%